2020
DOI: 10.21037/gs-20-249
|View full text |Cite
|
Sign up to set email alerts
|

Results of intraoperative radiotherapy given as a boost after breast conserving-surgery

Abstract: Background: Whole breast irradiation after breast-conserving surgery (BCS) with an external beam boost of 10-16 Gy is currently the standard treatment in breast cancer. Various modalities have been used for tumor bed boost irradiation. This study aimed to evaluate the local recurrence rate, overall survival rate (OSR), toxicity and cosmetic outcome of intraoperative radiotherapy (IORT) as a boost followed by whole breast irradiation in patients who received BCS.Methods: This is a retrospective study. Between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Nonetheless, interesting hypotheses could be pondered after these findings. Other experiences published along the last decade, assessing kIORT as a boost approach, have reached similar and encouraging outcomes with follow-up times between 28 and 78 months (14,(40)(41)(42)(43). In spite of recurrence risks, classical factors, such as patient age <50, higher T and clinical stages, ET, and ypN1 outcome, were related to increased failure rates.…”
Section: Discussionmentioning
confidence: 79%
“…Nonetheless, interesting hypotheses could be pondered after these findings. Other experiences published along the last decade, assessing kIORT as a boost approach, have reached similar and encouraging outcomes with follow-up times between 28 and 78 months (14,(40)(41)(42)(43). In spite of recurrence risks, classical factors, such as patient age <50, higher T and clinical stages, ET, and ypN1 outcome, were related to increased failure rates.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, production of collagen is reduced due to restrained fibroblast proliferation and the risk of wound infections is elevated as a result of the impaired immune system [ 36 ]. However, adjuvant chemotherapy was shown to have no impact on chronic higher-grade toxicities in patients treated with IORT and WBRT [ 37 , 38 ]. Moreover, a retrospective analysis of patients who received neoadjuvant chemotherapy and subsequently underwent IORT and EBRT did not reveal any severe acute and late toxicity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many single-arm studies have demonstrated the efficacy and safety of IORT boost+WBI; [33][34][35][36][37][38][39][40][41][42][43] however, comparative studies on IORT boost+WBI and conventional radiotherapy are still lacking. Through a search of major databases, we screened nine comparative studies of IORT boost+WBI versus conventional radiotherapy, with varying results.…”
Section: Discussionmentioning
confidence: 99%